Penyuluhan Menyikapi Kondisi Pandemi Corona dengan Hidup Sehat dan Makan Makanan Bergizi - Feti Fatonah; Suse Lamtiar; Dian Anggraini Purwaningtyas; Lia Retno; Ai Dewi Kosmala (Politeknik Penerbangan Indonesia Curug, 2021)
Currently a plague all over the word makes people feel hopeless and even think about suicide. This condition is exacerbated by the many layoffs from companies. Some housewives feel hopeless in responding to this pandemic, they think about how to deal with conditions to keep the body fit, with maintain family health amidst this pandemic as well as regulate a balanced nutritional diet wth minimal finances. Of course this is not easy for some housewives. Why do housewives choose? Because the financial manager who regulates food patterns during pandemic conditions is a housewife. In responding to the pandemic, the Indonesian Avition Polytechnic has participated in reducing the impact of the pandemic, one of which is through counseling activities, which are carried out by lecturers in community service activities to housewives, Dharma Wanita members the PPIC around the Indonesian Polytechnic campus, namely in serdang wetan village, Legok sub-district, Tangerang district. This PKM activity is a medium that connects the word of education with the surrounding community, this PKM activity is carried out by providing counseling to mothers around the PPIC campus, it is hoped that this activity will add insight to housewives that the current pandemic conditions cannot be faced only by panic but it must be with the knowledge and insight to get around a varied diet and balanced nutrition without being expensive, and invite family members to always live a healthy life, so that the body’s immunity increases, so that you can avoid the corona virus.